2014
DOI: 10.1098/rstb.2013.0134
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 promotes the stabilization of young synaptic contacts

Abstract: Maintaining a population of stable synaptic connections is probably of critical importance for the preservation of memories and functional circuitry, but the molecular dynamics that underlie synapse stabilization is poorly understood. Here, we use simultaneous time-lapse imaging of post synaptic density-95 (PSD-95) and Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) to investigate the dynamics of protein composition at axodendritic (AD) contacts. Our data reveal that this composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Consistently, these results showed season-dependent properties, and the winter PM 2.5 sample caused the most obvious changes. The synapse is the key structure in mediating information transmission between neurons and synaptic degeneration is an early event in neurodegenerative diseases (Taft et al, 2013). Knockdown of the PSD-95, one of the PSD-related proteins, caused synaptic changes and enhanced long-term potentiation , thereby decreasing the abilities of learning and memory (Hölscher, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, these results showed season-dependent properties, and the winter PM 2.5 sample caused the most obvious changes. The synapse is the key structure in mediating information transmission between neurons and synaptic degeneration is an early event in neurodegenerative diseases (Taft et al, 2013). Knockdown of the PSD-95, one of the PSD-related proteins, caused synaptic changes and enhanced long-term potentiation , thereby decreasing the abilities of learning and memory (Hölscher, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore spine elongation and thinning in CD44-depleted cells can indicate their juvenilization. The lower level of PSD-95 in dendritic spines observed upon CD44 knockdown may also explain such a “less mature” phenotype because PSD-95 has been shown to promote synaptic maturation and stabilization (Taft and Turrigiano, 2014). Of interest, we observed a decrease in the frequency of AMPA receptor–mediated mEPSCs, together with no changes in mEPSCs amplitude upon CD44 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In organotypic slice cultures, this process is much longer, and can take up to 24 hours (De Roo et al, 2008; Lambert et al, 2017). In these studies, the recruitment of PSD-95-GFP has been shown to be dependent on synaptic activity (De Roo et al, 2008; Taft and Turrigiano, 2014) and required for the activity dependent stabilization of excitatory synapses and spines (Ehrlich et al, 2007), so much so, that its presence provides an excellent prediction for which spines will be stabilized (De Roo et al, 2008; Ehrlich et al, 2007; Taft and Turrigiano, 2014). Interestingly, the increase in PSD-95 levels that accompanies spine enlargement after LTP induction has a similar time delay to that of PSD-95 accumulation after contact between a nascent spine and its presynaptic partner (Bosch et al, 2014; Meyer et al, 2014).…”
Section: Psd-95 Recruitment Is Key To Synaptic Maturation and Spine Smentioning
confidence: 99%